1992
DOI: 10.1597/1545-1569(1992)029<0015:clapit>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Cleft Lip and Palate in Tehran

Abstract: Seventy-nine cleft lip and/or palate births were isolated from 21,138 live births between January 1, 1983 and December 31, 1988 in one hospital in Tehran. Among these, 21 (26.58 percent) were cleft lip (CL), 45 (56.96 percent) were cleft lip and palate (CLP), and 13(16.45 percent) were cleft palate (CP). Chemical sulfur mustard gas was indicated as a major factor in 30 (37.97 percent) of the bilateral cleft lip and palate infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 0 publications
1
7
0
1
Order By: Relevance
“…Clefts of the lip and/or palate (CL/P) are the most common congenital anomalies to affect the orofacial region. The epidemiology of CL/P has been studied extensively in various populations and ethnic groups (Menegotto and Salzano, 1991; Taher, 1992; Gregg et al, 1994; Kozelj, 1996; Murray et al, 1997; Hagberg et al, 1998; Shapira et al, 1999; Cooper et al, 2000; Msamati et al, 2000; Natsume et al, 2000a; Rajabian and Sherkat, 2000; Kim et al, 2002; Sipek et al, 2002; Blanco-Davila, 2003, Elahi et al, 2004; Magdalenic-Mestrovic and Bagatin, 2005; Suleiman et al, 2005; Gundlach and Maus, 2006; Jamilian et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Clefts of the lip and/or palate (CL/P) are the most common congenital anomalies to affect the orofacial region. The epidemiology of CL/P has been studied extensively in various populations and ethnic groups (Menegotto and Salzano, 1991; Taher, 1992; Gregg et al, 1994; Kozelj, 1996; Murray et al, 1997; Hagberg et al, 1998; Shapira et al, 1999; Cooper et al, 2000; Msamati et al, 2000; Natsume et al, 2000a; Rajabian and Sherkat, 2000; Kim et al, 2002; Sipek et al, 2002; Blanco-Davila, 2003, Elahi et al, 2004; Magdalenic-Mestrovic and Bagatin, 2005; Suleiman et al, 2005; Gundlach and Maus, 2006; Jamilian et al, 2007).…”
mentioning
confidence: 99%
“…Although the epidemiology of CL/P has been studied in many populations and countries, few epidemiologic studies have been performed in Iran, and their results are conflicting. In a study evaluating the epidemiology of CL/P in Iran, Taher (1992) reported a birth prevalence of 3.73 per 1000. Jamilian et al (2007) reported a birth prevalence of 2.14 per 1000 for CL/P in Iran.…”
mentioning
confidence: 99%
“…Although they had used his cases as their own controls, and thus reduced selection bias, they did not adjust for the effect of parents' increasing age on malformation occurrence. Taher et al[28] claimed that the use of mustard gas in the Iran-Iraq conflict might have increased the number of cleft lip and cleft palate in children, however, they were not able to establish any causal effect between these two events, nor could they exclude the effects of other possible causes.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, it has been recognized as a radiomimetic (5) and a human carcinogen (24,26). It may also be teratogenic and mutagenic (27,28). Mustard is an alkylating agent, and once absorbed, its toxic effects result from chemical reactions with cellular constituents.…”
Section: Ch2-ch2-ci S Ch2-ch2-cimentioning
confidence: 99%